Constraints on dark energy dynamics and spatial curvature from Hubble parameter and baryon acoustic oscillation data. Issue 1 (19th July 2018) - Ryan, Joseph; Doshi, Sanket; Ratra, Bharat
ABSTRACT: We use all available baryon acoustic oscillation distance measurements and Hubble parameter data to constrain the cosmological constant Λ, dynamical dark energy, and spatial curvature in simple cosmological models. We find that the consensus spatially flat ΛCDM (Λ cold dark matter) model provides a reasonable fit to the data, but depending on the Hubble constant prior and cosmological model, it can be a little more than 1σ away from the best-fitting model, which can favour mild dark energy dynamics or non-flat spatial hypersurfaces.